2018
DOI: 10.2298/pan141102007i
|View full text |Cite
|
Sign up to set email alerts
|

Current account sustainability: A non-linear comparative empirical overview

Abstract: This study aims to examine the sustainability of current account deficits for Hungary, Poland, Czech Republic and Turkey over the period 1998Q1:2014Q2, with a special attention to the Turkish case, by applying the theoretical model of Steven Husted (1992). The main motive for the choice of time span is that the period comprises the outcomes of two important crises Turkish economy experienced in 2001 and 2008. The empirical testing procedure of the sustainability is twofold so as to be linear and non-linear. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…They should stimulate the competitiveness of the goods and services on the international markets. According to Iyidogan and Turan (2018), more saving friendly policies would be helpful in addressing this structural problem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They should stimulate the competitiveness of the goods and services on the international markets. According to Iyidogan and Turan (2018), more saving friendly policies would be helpful in addressing this structural problem.…”
Section: Resultsmentioning
confidence: 99%
“…Afonso et al (2017) assesses the sustainability of the CA balance and external debt in a sample of EU countries and find that sustainability is not rejected for Austria, Belgium, Denmark, Estonia, and Germany and that there is concern about the sustainability of external debt in Latvia, Greece, Portugal, Romania, Estonia, and Lithuania. Iyidogan and Turan (2018) found that in Turkey, Poland and the Czech Republic CA deficit is not sustainable, whereas in Hungary the results are mixed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Topalli and Dogan (2016) estimate two‐regime Markov switching regression model between exports and imports of Turkey and find weak form of sustainability of the current account over the period 1990Q1‐2014Q2. Iyidoğan and Turan (2018) test cointegration relationship between imports and exports of Turkey using Gregory–Hansen and Seo (2006) cointegration methods and find no evidence of sustainability for the Turkish current account deficit over the period 1998Q1‐2014Q2. Furthermore, many researchers analyse the sustainability of the Turkish current account by using current account to GDP ratio which allows for more comprehensive findings.…”
Section: Literature Review On the Current Account Sustainability Of Turkeymentioning
confidence: 99%